Sustainability strategic plan (CSSAP) and carbon inventory tours - UiTM, UGC (UiTM Green Centre, 2025)
UGC members visiting UiTM Raub campus in a series of sustainability strategic plan (CSSAP) and carbon inventory tours. The visit was led by the Director of UGC, Prof Madya Ts Khairi Khalid was warmly received by the Assistant Rector, Dr Saharani Abdul Rashid.